Psychological Predictors of Mortality Awareness: Time Perspective, Contentment With Age and Paternal Antipathy and Neglect. (May 2022) - Willoch, Therese C. F.; McDermott, Mark R.
Much research has focused upon the association between mortality awareness and mental ill-health. In this study we attempt to explore positive as well as negative psychological concomitants of mortality awareness. 170 participants were recruited in an online questionnaire study, measuring seven independent variables - marginalisation, childhood adversity, rebelliousness, time perspective, attitudes toward age and stage of life, health attitudes and demographics - and five dependent variables, specifically mortality legacy, mortality fearfulness, mortality acceptance, mortality disempowerment and mortality disengagement. Several significant bivariate associations were found. Follow-up regression analysis observed combined effects of variables accounting for 28% of variance in mortality legacy, 27% for mortality fearfulness, 13% for mortality acceptance, 42% for mortality disempowerment and 25% for mortality disengagement. Time perspective, contentment with age, and paternal antipathy and neglect were the most notable independent predictors. It was concluded that attitudes towards health, stage of life and childhood experiences significantly predict mortality awareness.